Prediksi Volume Weighted Average Price Saham INDF Menggunakan Algoritma Genetika - Firdaus, Liony Putri; Ahmad, Defri (Jurnal Matematika; Vol 14 No 1 (2024), 2024)
In the era of industrial revolution 4.0, investors in almost all countries are interested in investing in stocks. The wrong investment decision in deciding when it is the right time to buy and sell shares can cause big losses for investors. Therefore, technical analysis is required. One of the technical indicators used in intraday trading is the volume-weighted average price (VWAP). To predict the VWAP accurately in stock trading transactions, a genetic algorithm is used. The stocks that are suitable to be selected for conducting stock trading transactions are PT. Indofood Sukses Makmur Tbk. This research is applied research that uses secondary data from the website of PT. Indofood Sukses Makmur Tbk. The results showed that the predictive results of the VWAP testing data for PT. Indofood Sukses Makmur Tbk are close to actual data, which means that the genetic algorithm has good predictive abilities with an accuracy rate of 99.7% (very high method accuracy).